An Error Analysis of English Education Students' Academic Essays - Tuparan, Roem T.; Caturay Jr., Warlito S. (Silliman Journal, 2024)
Error analysis is a process that allows the examination of language learners' errors and their sources. This type of investigation guided this study to examine 74 academic essays of second-year level English-major students taking Bachelor of Secondary Education in a state university in Negros Occidental, Philippines. Based on Gustilo and Magno’s framework (2012), 1,271 errors were identified. Of these, the most frequent error types relate to using commas, structuring sentences, verb tenses, prepositions, and word choices. In identifying the sources of these errors, Brown’s framework was used. Data reveal that many of these errors stem from intralingual transfer, indicating the learners’ incorrect application of the rules of English in their writing. Additionally, the errors in the paper were also described using the adapted frameworks of Corder and Dulay et al. Majority of the errors can be described as misinformation. The results of this study provide many pedagogical implications.